Origins of spontaneous activity in the degenerating retina - Trenholm, Stuart; Awatramani, Gautam B. (Frontiers in Cellular Neuroscience, 2015)
Sensory deafferentation resulting from the loss of photoreceptors during retinal degeneration (rd) is often accompanied by a paradoxical increase in spontaneous activity throughout the visual system. Oscillatory discharges are apparent in retinal ganglion cells in several rodent models of rd, indicating that spontaneous activity can originate in the retina. Understanding the biophysical mechanisms underlying spontaneous retinal activity is interesting for two main reasons. First, it could lead to strategies that reduce spontaneous retinal activity, which could improve the performance of vision restoration strategies that aim to stimulate remnant retinal circuits in blind patients. Second, studying emergent network activity could offer general insights into how sensory systems remodel upon deafferentation. Here we provide an overview of the work describing spontaneous activity in the degenerating retina, and outline the current state of knowledge regarding the cellular and biophysical properties underlying spontaneous neural activity.